A new species and a key to eleven species of the genus Conophyma Zubovsky, 1898 (Orthoptera, Acridoidea, Catantopidae, Conophyminae) from China - Liu, Yu-Sheng; Sun, Daqing; Zhang, Jinyu; Yin, Zhan (Zootaxa, 2021)
A new species and a key to eleven species of of the genus Conophyma Zobovsky, 1898 from China is described in this paper. The new species Conophyma lini sp. nov. is similar to C. xiai Zhang et al, 2015, but differs from latter by: vertex longer, apex narrower; minimum width of interspace 1.6 times length in mesosternum; posterior margin of epiproct waved, with angular projection in the middle, furculae small and width of Epiphallus 2.5 times high. Type specimens are deposited in the Northwest Plateau Institute of Biology, Chinese Academy of Sciences, Xining, Qinghai 810001, China.